Einladungskarte für das Museum of Popular Art im Palast des Ataoja in Osogbo, auch Osogbo Museum genannt (Of Art Worlds - Collecting and Archiving Modern and Contemporary Art on the African Continent, 2013)
Copyright jointly or exclusively held by Iwalewahaus, CBCIU and/or Georgina Beier Estate Executor. CBCIU and Iwalewahaus identifiers currently unavailable.
Keywords: Museums; Art; Africa; Exhibitions; Invitation cards; Art Exhibition; Ataoja; Osogbo; Nigeria; Cultural Centre; Performing Arts Center